Knowledge of Medicinal Plants and Their Benefits to the Niyamagiri Hill Tribe Community, Kalahandi District, Odisha, India - Sangeeta Das; Shaikh Ameeruddin; Sivaprasad Das; A. Leelaveni (Contemporary Research and Perspectives in Biological Science Vol. 5, 2024)
Aim: The current study was prepared to collect ethnomedicinal data from tribal peoples in the Niyamagiri hill region of Kalahandi district, Odisha, India. The tribals of this region have been using medicinal plants to treat various kinds of diseases since time immemorial. Background: Traditional medicine implementations involve therapeutic methods using predictable medicines that have been used orally through generations. In view of indigenous segregation over several years, these apply to different groups and communities, which have continued to date. Methods: To the study records the information on the medicinal uses of plants by leading healers by conducting interviews and recording comprehensive knowledge about the medicinal properties of different plants with the snowball technique and sampling method. Plants were recognized by the local practitioner also known as Kabi Raja or Vaidya, on the forest floor and were classified botanically. Results: The present study recorded the use of different parts of 150 plant species belonging to 131 genera of 78, unlike flowering plant families, against various diseases, with special reference to diarrhoea, dysentery, cold, cough, piles and fever. The practitioners use these plants to treat kinds of ailments like asthma, skin diseases, piles, constipation, diabetes, fever, cough, toothache, wound healing, headache, infertility in women, mouth ulcers, stomach disorders, indigestion, insect bites, ring worms, thirst, eczema, dysentery and diarrhoea. Since there are no contemporary medical facilities nearby, all of these medicinal plants are employed as sources of healing. Each of these plants has a unique lclimate that promotes growth, especially in the district’s hilly woodland. The current record of ethnomedicinal data specified that the backward and tribal local people commonly used plants for the treatment of diarrhoea and dysentery are A. salvifolium, A. spinosus, A. paeoniifolius, A. paniculata, B. acutangula, B. purpuria, B. malabarium, B. pinnatum, B. lanzan, C. arborea, C. fistula. For cold and cough the plants are A. indica, A. sativum, A. galanagal, A. mexicana, A. integrifolia, B. acutangula, B. campestris, B. pinnatum. Conclusion: The use of herbal therapies, their advantages, side effects and other details almost have the same traditional values as the previous workers with a little difference. The efficiency and safety of all the listed ethnomedicinal plants need to be evaluated for phytochemical studies.